Análisis de Factores Socioeconómicos y su Impacto en la Delincuencia en el Cantón Celica - Campoverde Patiño, Angélica María (2024)
The present work of curricular integration had the objective of analyzing the socioeconomic factors and their impact of crime in the canton Celica, in order to know what are the delinquency margins that in the last three years have developed in this canton of the province of Loja; it has been decided to take a quantitative approach for the best description of the data, to identify the relationship between the variables of studies, two physical surveys were applied, one to trained personnel such as: Police, military, security guards and lawyers; and the other to the general population in order to determine, the impact of crime in the Celica canton, and how it affects the social and economic sphere; causing enormous consequences, since it is evident that in the last three years has been considerable increase in crime in this sector, in view that there has been an influx of foreigners such as: Venezuelans and Colombians, to our country, who have sought refuge in small towns, bringing with it an increase in insecurity in places that in the past were considered quiet. As a result, the socioeconomic factors do have an impact on the high crime rates, although the State has invested in citizen security, we clearly see that it has not obtained the best results in reducing the problem and crime continues to contaminate small cities such as Celica.